2004
DOI: 10.1186/1472-6904-4-5
|View full text |Cite
|
Sign up to set email alerts
|

S-allylmercaptocysteine scavenges hydroxyl radical and singlet oxygen in vitro and attenuates gentamicin-induced oxidative and nitrosative stress and renal damage in vivo

Abstract: BackgroundOxidative and nitrosative stress have been involved in gentamicin-induced nephrotoxicity. The purpose of this work was to study the effect of S-allylmercaptocysteine, a garlic derived compound, on gentamicin-induced oxidative and nitrosative stress and nephrotoxicity. In addition, the in vitro reactive oxygen species scavenging properties of S-allylmercaptocysteine were studied.ResultsS-allylmercaptocysteine was able to scavenge hydroxyl radicals and singlet oxygen in vitro. In rats treated with gent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 49 publications
5
87
1
Order By: Relevance
“…Consistent with the data from the study of Pedraza-Chaverrí et al 40) we observed in our study that urinary excretion of total protein was increased after GM injection indicating tubular damage. On the other hand, BUN and serum creatinine levels were augmented indicating glomerular damage.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with the data from the study of Pedraza-Chaverrí et al 40) we observed in our study that urinary excretion of total protein was increased after GM injection indicating tubular damage. On the other hand, BUN and serum creatinine levels were augmented indicating glomerular damage.…”
Section: Discussionsupporting
confidence: 83%
“…However, the combined administration of quercetin plus GM to rats resulted in significant reduction in the elevated levels of urinary total protein concentrations, BUN and serum creatinine. These results could be in accord with several other researches, which reported that, compounds with antioxidant properties like S-allylmercaptocysteine 40) and diallyl sulfide 41) inhibited the increased urinary excretion of total protein induced by GM in rats. Other compounds like resveratrol, 22) carnosine 23) or garlic extract, 8) partially prevented the increase in BUN and serum creatinine levels induced by GM.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[17,18] Singlet oxygen ( 1 O 2 ) was generated in vitro by reacting NaOCl and H 2 O 2 and the bleaching of N, N-dimethyl-4-nitrosoaniline (RNO) was monitored at 440 nm. The reaction mixture contained 45 mM phosphate buffer (pH 7.1), 50 mM NaOCl, 50 mM H 2 O 2 , 50 mM histidine, 10 µM RNO and various concentrations (0-200 µg/ml) of ECME in a final volume of 2 ml.…”
Section: Singlet Oxygen Scavenging Assaymentioning
confidence: 99%
“…The disruption of BUN and creatinine secretion at the renal proximal tubules will result in rising plasma BUN and creatinine level. This is due to the damage on the glomerulus, leading to a lowering of glomerular filtration rate (GFR) followed by rising plasma BUN and creatinine level [9].…”
Section: Introductionmentioning
confidence: 99%